Effect of positive and negative dimensions of mental imagery and self-talk on learning of soccer kicking skill - Gholamreza Lotfi; Farshid Tahmasbi; Mohammad Hossein Forghani; Andrzej Szwarc (Physical Education of Students)
Background and Study Aim. Mental imagery and self-talk are two important mental skills that are used for improvement of performance and learning of motor and sport skills. This study aimed to investigate the effect of positive/negative mental imagery and positive/negative self-talk on learning of soccer kicking skill.